2015
DOI: 10.3390/f6041343
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Planting Density on Knot Attributes and Branch Occlusion of Betula alnoides under Natural Pruning in Southern China

Abstract: Knot-related defects are the major cause of timber quality degradation, and diminishing this kind of defects is an important issue in forest management. For the purpose of clear-wood production, knot attributes and branch occlusion of Betula alnoides under natural pruning were investigated in a 14-year-old experimental plantation with five planting densities ranging from 500 to 3333 stems per hectare in southern China, and a total of 1325 occluded branches from 30 trees were sampled and dissected. The mean occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 34 publications
1
14
0
1
Order By: Relevance
“…5), reducing branch diameter and accelerating stem growth rate appear to be essential for shortening branch occlusion time, especially in natural pruning. It is widely known that branch diameter is closely correlated with planting density (Mäkinen, 2002;Kearney et al, 2007;Hein et al, 2008;Newton et al, 2012;Wang et al, 2015), and that stem diameter growth rate could be accelerated by thinning unwanted competitors and fertilizing the pruned trees (Wiseman et al, 2009;Forrester et al, 2012). Therefore, combining artificial pruning with these measures might further shorten branch occlusion time and rotation length for clear-wood production.…”
Section: Branch Occlusion Timementioning
confidence: 97%
See 2 more Smart Citations
“…5), reducing branch diameter and accelerating stem growth rate appear to be essential for shortening branch occlusion time, especially in natural pruning. It is widely known that branch diameter is closely correlated with planting density (Mäkinen, 2002;Kearney et al, 2007;Hein et al, 2008;Newton et al, 2012;Wang et al, 2015), and that stem diameter growth rate could be accelerated by thinning unwanted competitors and fertilizing the pruned trees (Wiseman et al, 2009;Forrester et al, 2012). Therefore, combining artificial pruning with these measures might further shorten branch occlusion time and rotation length for clear-wood production.…”
Section: Branch Occlusion Timementioning
confidence: 97%
“…Reducing dead knot-related defects has been an important issue in the production of highquality timber. A number of studies have shown that the size of dead knot under natural pruning was significantly and positively correlated with branch diameter and stem diameter growth (Hein and Spiecker, 2007;Hein, 2008;Wang et al, 2015). The incidence and size of decay or discoloration also increased with increasing branch diameter (Gerrand et al, 1997;Wardlaw and Neilsen, 1999;Wiseman et al, 2006;Sandi et al, 2012), dead branch stub length and branch occlusion time (Metzler, 1997;Dȃnescu et al, 2015).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Along with the pruned branch stub length and radial growth of the tree, the diameter of a pruned branch is an important factor influencing the time needed for the occlusion of a knot independent of the tree species (Verkasalo and Rintala 1998;DeBell et al 2006;Kannisto and Heräjärvi 2006;Hein and Spiecker 2007;Hein 2008;Dănescu et al 2015;Wang et al 2015Wang et al , 2016Sheppard et al 2016;Stener et al 2017). According to our study, approximately 70-80% of the diameter of an average knot stub was covered in birch trees with the average growth rate in five to six years.…”
Section: Occlusion Rate Of Study Knotsmentioning
confidence: 99%
“…This has also been demonstrated for a large quantity of species with a specific focus on branch and knot development [4,[7][8][9][10]. For artificial commercial forests, producing high quality wood should also be economically viable.…”
Section: Introductionmentioning
confidence: 99%